Perbedaan Individual pada Ideologi Politik Berbasis Agama - Amalia, Ilmi (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2020)
AbstractIn practicing worship almost all Muslims run in the same manner but in Indonesia also found the diversity of the face of Islam. One form of diversity is how to see religion as a political ideology. From various views political ideologies based on Islamic religion have polarizations, namely secular and radical Islamism. How to explain the diversity of ideologies based on individual differences. Jost et al (2009) offer three basic needs that determine individual ideological differences, namely the need for epistemic, the need for existential, and the need for relational. In addition to differences in the concept of fundamental needs, studies also show a relationship between personality types and ideological or political attitudes. Duckitt & Sibley (2010) offers a dual-process motivational model that explains that political ideology is formed due to interactions between personalities and different social situations. Many studies have been conducted to see the relationship between ideology with liberal and conservative polarization (right / left) or right wing authoritarianism (RWA) and social dominance orientation (SDO) with different needs or personality types (Jost, Ledgerwood, & Hardin, 2008; Jost et al., 2007; Sibley, Osborne, & Duckitt, 2012). However, no research has been conducted on political ideologies based on religion, especially Islam. The study was conducted on 243 Muslims and aged 17 years and over. Questionnaires were distributed in the Greater Jakarta area online and offline. The sampling technique used convenience sampling. Then the data is processed using regression analysis techniques. The results showed that together, the need for epistemic, need for existential, need for relational, and Big five personality influenced Islamic political ideology with a contribution of 7.2%. Significant predictors of the relationship are need for existential and need for relational.Â AbstrakDalam pelaksanaan ibadah hampir semua umat Islam menjalankan dengan tata cara yang sama namun di Indonesia ditemukan juga keanekaragaman wajah Islam. Salah satu bentuk keanekaragaman tersebut adalah bagaimana melihat agama sebagai suatu ideologi politik. Dari berbagai macam pandangan dapat dilihat bahwa ideologi politik yang berbasis agama Islam memiliki polarisasi yaitu sekuler dan radikal Islamisme. Bagaimana menjelaskan keragaman ideologi tersebut berdasarkan perbedaan individual. Jost dkk (2009) menawarkan adanya tiga kebutuhan mendasar yang menentukan perbedaan ideologi individu yaitu need for epistemic, need for existential, dan need for relational. Selain pada perbedaan pada konsep kebutuhan mendasar, studi juga menunjukkan adanya hubungan tipe kepribadian dan ideologi atau sikap politik. Duckitt & Sibley (2010) menawarkan model dual-process motivational yang menjelaskan bahwa ideologi politik terbentuk akibat interaksi antara kepribadian dan situasi sosial yang berbeda. Studi telah banyak dilakukan untuk melihat hubungan ideologi dengan polarisasi liberal dan konservatif (kanan/kiri) atau right wing authoritarianism (RWA) dan social dominance orientation (SDO) dengan perbedaan kebutuhan atau tipe kepribadian (Jost, Ledgerwood, & Hardin, 2008; Jost et al., 2007; Sibley, Osborne, & Duckitt, 2012). Namun demikian, belum ada riset yang dilakukan pada ideologi politik yang berlandaskan pada agama terutama Islam. Studi dilakukan pada 243 Muslim dan berumur 17 tahun ke atas. Kuesioner disebarkan di daerah Jabodetabek secara daring dan luring. Teknik pengambilan sampel digunakan convenience sampling. Kemudian data diolah dengan teknik analisis regresi. Hasil penelitian menunjukkan secara bersama-sama, need for epistemic, need for existential, need for relational, dan Big five personality mempengaruhi ideologi politik Islam dengan kontribusi sebesar 7,2 %. Prediktor yang signifikan hubungannya adalah need for existential dan need for relational.